Asymmetric reconfiguration of a 3-dof parallel manipulator - Balmaceda-Santamaría, A. L.; Chávez-Toruño, A. E. (Nexo Revista Científica, 2020)
In this paper an asymmetric reconfigurable parallel manipulator is presented. Asymmetric configurations are obtained by modifying the angle between each of the kinematic chains. Thanks to the reconfiguration proposal significant improvement of the manipulator performance can be obtained with respect to a Delta-type parallel robot. The computation of the best condition number is obtained, the results show that by using the redundancy, all the performance indices that depend on the Jacobian matrix can be improved as well.